2020
DOI: 10.1039/d0tc01693d
|View full text |Cite
|
Sign up to set email alerts
|

Synergy effect of co-doping Sc and Y in Sb2Te3 for phase-change memory

Abstract: Co-doping Sc and Y is a feasible way to obtained better-performance and moderate-cost Sb2Te3 phase-change materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…In addition to the commonly used germanium alloying, a large proportion of main‐group and transition‐metal elements in the periodic table have been screened, both in simulations and experiments, with scandium and yttrium emerging as the optimal dopants. [ 10 ] Codoping with Sc and Y was found to be a synergistic approach to further improve the properties of Sb 2 Te 3 for PCM applications, [ 11 ] whereas nanostructuring at the device level, such as forming alternating layers of Sb 2 Te 3 and TiTe 2 , was found to have a dramatic impact on reducing the time‐dependent resistance drift and improving the stability of the amorphous state. [ 12 ] Because of all of these recent results, Sb 2 Te 3 has come to the forefront of PCM technology.…”
Section: Figurementioning
confidence: 99%
“…In addition to the commonly used germanium alloying, a large proportion of main‐group and transition‐metal elements in the periodic table have been screened, both in simulations and experiments, with scandium and yttrium emerging as the optimal dopants. [ 10 ] Codoping with Sc and Y was found to be a synergistic approach to further improve the properties of Sb 2 Te 3 for PCM applications, [ 11 ] whereas nanostructuring at the device level, such as forming alternating layers of Sb 2 Te 3 and TiTe 2 , was found to have a dramatic impact on reducing the time‐dependent resistance drift and improving the stability of the amorphous state. [ 12 ] Because of all of these recent results, Sb 2 Te 3 has come to the forefront of PCM technology.…”
Section: Figurementioning
confidence: 99%
“…S7 †). [53][54][55] Despite the low degree of graphitization according to the XRD and Raman results, XPS results conrm a large content of sp 2 character in p aromatic form. The presence of such sp 2 in p aromatic system could enhance electric conductivity 32 which is desired in applications to supercapacitors.…”
Section: View Article Onlinementioning
confidence: 99%
“…Ab initio materials screening studies have recently shown that alloying with a suitable element, such as Sc [10][11][12][13][14][15] or Y [16][17][18][19] , can largely increase the nucleation rate to improve switching speed at elevated temperatures. The recently designed Sc 0.2 Sb 2 Te 3 (SST) alloy brings the programming time down to~0.7 ns, expanding the capability of PRAM for cache-type memory applications [10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%